# (9) 10H 10- 10F -10 -5 10 -10 .5 10 -10 10 -5 -10 -5 -10F -10- -10 -10F O f(x) = -2x + 4 o f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x + 4 O f(x) = -2x2 – 7x -2x2 - 7x O f(x) O f(x) = -2x2 -2x2 - 7x O f(x) = 7x 5x2 -* + 5x2 o f(x) = - * o f(x) = - + 5x2 3 O f(x) + 5x2 o f(x) 3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x³ O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x2 – O f(x) = x2 - 3x - 3x O f(x) = x2 - 3x O f(x) = x2 - 3x O f(x) = 2x3 - 3x + 1 2x3 – 3x + 1 O f(x) 2x3 O f(x) O f(x) = 2x3 - 3x + 1 - 3x + 1 %3D o Ax) = - o Pa) = + x? - 4 + x? - + x2 - 3 o Rx) = - + x2 3 O f(x) + x2 - O f(x) = - 3 - 2r3 + x o fx) = - 2x3 +x 9. -х o (x) = 5 - 2x3 + O f(x) = (d) (b) y (f) У (h) y y 10- 10- 10- 10 х -10 -5 10 10 -10 -5 -10 -10 -5 -5 -10- -10F -10- -10- o f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x2 – 7x O f(x) = -2x² – 7x O f(x) -2x2 7x O f(x) = -2x2 - 7x 1,4 + 5x2 3 글 + 5x2 o f(x) o f(x) = - O f(x) + 5x2 5x2 O f(x) = - O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x2 - 3x O f(x) = x2 - 3x O f(x) = x2 - 3x · 3x O f(x) = x2 2x3 - 3x + 1 O f(x) = 2x3 - 3x + 1 O f(x) O f(x) = 2x3 - 3x + 1 O f(x) = 2x3 - 3x + 1 %3D o Rw) = - * - o M) = - Rx) = - + x2 - 4 + x2 O (x) 4 + x² - O f(x) O f(x) 3 3 3 x5 - 2x3 +. 2x3 9. o f(x) RA) = 5 - 2x3 +. O Fx) = 5 - 2x3 O (x) = O f(x) - 5

Question

Match the polynomial function with its graph: [A] through [H]

1 Rating

### Want to see this answer and more?

Experts are waiting 24/7 to provide step-by-step solutions in as fast as 30 minutes!*

*Response times may vary by subject and question complexity. Median response time is 34 minutes for paid subscribers and may be longer for promotional offers.
Tagged in
Math
Calculus
Transcribed Image Text

(9) 10H 10- 10F -10 -5 10 -10 .5 10 -10 10 -5 -10 -5 -10F -10- -10 -10F O f(x) = -2x + 4 o f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x + 4 O f(x) = -2x2 – 7x -2x2 - 7x O f(x) O f(x) = -2x2 -2x2 - 7x O f(x) = 7x 5x2 -* + 5x2 o f(x) = - * o f(x) = - + 5x2 3 O f(x) + 5x2 o f(x) 3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x³ O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x2 – O f(x) = x2 - 3x - 3x O f(x) = x2 - 3x O f(x) = x2 - 3x O f(x) = 2x3 - 3x + 1 2x3 – 3x + 1 O f(x) 2x3 O f(x) O f(x) = 2x3 - 3x + 1 - 3x + 1 %3D o Ax) = - o Pa) = + x? - 4 + x? - + x2 - 3 o Rx) = - + x2 3 O f(x) + x2 - O f(x) = - 3 - 2r3 + x o fx) = - 2x3 +x 9. -х o (x) = 5 - 2x3 + O f(x) = (d) (b) y (f) У (h) y y 10- 10- 10- 10 х -10 -5 10 10 -10 -5 -10 -10 -5 -5 -10- -10F -10- -10- o f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x + 4 o f(x) = -2x + 4 O f(x) = -2x2 – 7x O f(x) = -2x² – 7x O f(x) -2x2 7x O f(x) = -2x2 - 7x 1,4 + 5x2 3 글 + 5x2 o f(x) o f(x) = - O f(x) + 5x2 5x2 O f(x) = - O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x4 + 3x3 O f(x) = x2 - 3x O f(x) = x2 - 3x O f(x) = x2 - 3x · 3x O f(x) = x2 2x3 - 3x + 1 O f(x) = 2x3 - 3x + 1 O f(x) O f(x) = 2x3 - 3x + 1 O f(x) = 2x3 - 3x + 1 %3D o Rw) = - * - o M) = - Rx) = - + x2 - 4 + x2 O (x) 4 + x² - O f(x) O f(x) 3 3 3 x5 - 2x3 +. 2x3 9. o f(x) RA) = 5 - 2x3 +. O Fx) = 5 - 2x3 O (x) = O f(x) - 5